Communication and its development in autism spectrum disorders - Paul, R. (Autism and Pervasive Developmental Disorders, Second Edition, 2007)
Introduction Communication deficits are one of the core symptoms of autism spectrum disorders (ASDs). People with ASD can be slow to begin talking, or may not learn to talk at all; others may learn to produce words and sentences but have difficulty using them effectively to accomplish social interactive goals. In this chapter we will discuss the course of the development of communication in ASD and will outline how communication deficiencies in this population are identified and treated. Before we do, however, we should be clear about three important terms we will be using, which are illustrated in Figure 4.1. The term “communication” is the broadest of this trio. It refers to all forms of sending and receiving messages, not only with language, but in other ways, such as with gestures, body language, even the way we dress. Animals can also communicate by means of their vocalizations to alert others to danger, for example. That's why the largest circle in Figure 4.1 represents communication. Within the realm of communication, language represents a specific type, so it is enclosed within the larger circle of communication in the figure. Language involves the creation of a potentially infinite set of never-before-conveyed messages through the combination of words in rule-governed ways that allow the formation of sentences to express meaning to others. © Cambridge University Press, 2007 and 2009.
Journal Abbreviation: Autism and Pervasive Developmental Disorders, Second Edition
Keywords: dept.cmd

Foreword - Paul, R. (Single-Word Reading: Behavioral and Biological Perspectives, 2007)
Keywords: dept.cmd

“Listen my children and you shall hear”: Auditory preferences in toddlers with autism spectrum disorders - Paul, Rhea; Chawarska, Katarzyna; Fowler, Carol; Cicchetti, Domenic; Volkmar, Fred (Journal of Speech Language and Hearing Research, 2007)
Purpose: This study tests the hypothesis that toddlers with autism spectrum disorders (ASD) will show differences from contrast groups in preferences for attending to speech. Method: This study examined auditory preferences in toddlers with ASD and matched groups of (a) typical age-mates, (b) age-mates with nonautistic developmental disabilities, and (c) younger children matched for language age. The experimental procedure measured time spent oriented to auditory stimuli that were created to exemplify language patterns that had been studied in typically developing infants. Results: Findings suggest that toddlers with ASD show a reduced preference for child-directed speech, compared with typical age-mates, but few differences from children with nonautistic developmental disorders. Correlational analysis revealed that time spent listening to child-directed speech by children with ASD was related to their concurrent receptive language ability as well as to receptive language abilities 1 year later. This relationship did not hold for the other groups. Conclusion: The present study supports the hypothesis that children with ASD perform differently from typical peers in auditory preference paradigms and that performance in these tasks is related to concurrent and later language development.
75 citations (Crossref) [2023-10-31] tex.eissn: 1558-9102 tex.unique-id: ISI:000250280300017
Keywords: *Attention; *Autistic Disorder/px [Psychology]; *Child Behavior; *Choice Behavior; *Infant Behavior; *Speech Perception; Attention; Auditory comprehension; Autism spectrum disorders; Autistic Disorder; Child Behavior; Child; Preschool; Choice Behavior; Comprehension; Female; Humans; Infant; Infant Behavior; Language Development; Language comprehension; Male; Speech Perception; article; auditory stimulation; auditory system; autism; controlled study; correlation analysis; dept.cmd; developmental disorder; female; human; language; language ability; language development; major clinical study; male; peer group; preschool child; speech; time; toddler

Increasing stroke patients' success in self-medication programs using an interdisciplinary cognitive rehabilitation approach. - Purdy, Mary (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2007)
Rehabilitation programs strive to help patients become more independent in all aspects of daily living. Therefore, management of a patient's healthcare requirements should be an integral part of the rehabilitation program, including management of medications. Some rehabilitation programs implement self-medication programs (SMP); however, patients with cognitive deficits are often excluded. This study explored whether patients with cognitive deficits due to stroke could successfully complete an SMP using an interdisciplinary cognitive rehabilitation approach. Twenty-seven stroke patients and 36 debilitated patients with cognitive deficits participated in an SMP. A nurse and a pharmacist educated patients on their medications, and a speech-language pathologist provided cognitive rehabilitation to the stroke patients, which incorporated information from the SMP. Eighty-one percent of the stroke patients successfully completed the SMP, compared to 36% of the debilitated patients. Thus, an interdisciplinary approach to medication management for cognitively impaired stroke patients holds promise.
3 citations (Crossref) [2023-10-31] Place: United States Purdy, Mary. Southern Connecticut State University, Department of Communication Disorders, USA. purdym1@southernct.edu
Keywords: *Cognition Disorders/rh [Rehabilitation]; *Patient Care Team/og [Organization & Administration]; *Patient Education as Topic/og [Organization & Administration]; *Self Administration; *Stroke/co [Complications]; Aged; Analysis of Variance; Case-Control Studies; Cerebrovascular Accident; Cognition Disorders; Cognition Disorders/et [Etiology]; Cognition Disorders/px [Psychology]; Curriculum; Humans; Length of Stay; Length of Stay/sn [Statistics & Numerical Data]; MLCS; MLOWN; Middle Aged; Needs Assessment; Nursing Assessment; Nursing Evaluation Research; Patient Care Team; Patient Education; Pharmacy Service; Hospital; Pharmacy Service; Hospital/og [Organization & Administration]; Problem Solving; Program Evaluation; Rehabilitation Nursing; Rehabilitation Nursing/og [Organization & Administration]; Self Administration; Self Administration/mt [Methods]; Self Administration/px [Psychology]; Severity of Illness Index; Speech-Language Pathology; Speech-Language Pathology/og [Organization & Administration]; Treatment Outcome; aged; analysis of variance; article; case control study; cerebrovascular accident; cognitive defect; curriculum; dept.cmd; drug self administration; evaluation; health care quality; hospital pharmacy; hospitalization; human; length of stay; methodology; middle aged; needs assessment; nursing assessment; nursing evaluation research; organization and management; patient care; patient education; problem solving; psychological aspect; rehabilitation nursing; speech disorder; statistics; treatment outcome

Ratings of communication competence by siblings of persons with Down syndrome - Smith, Sarah E.; Cascella, Paul W. (Education and Training in Developmental Disabilities, 2007)
This study surveyed 25 siblings of persons with Down Syndrome to gain an ecological perspective about important communication competence indicators. Siblings favorably described persons with Down Syndrome as “effective” and “good” communicators who “communicate to potential. “ Siblings regarded social communication skills as especially important, i.e., being able to communicate without fear, being able to express wants, needs, opinions, and feelings, being able to ask questions, and alerting partners to communication breakdowns. Siblings also regarded language comprehension as an important skill. Favorable descriptive labels were often applied to adult-aged persons with mild ID and normal hearing. Clinical implications are discussed focused on functional communication planning and implementation that takes into account the perspectives of family members, teachers, and rehabilitation personnel.
Citation Key Alias: lens.org/178-041-737-828-555 tex.unique-id: [object Object]
Keywords: dept.cmd; ⛔ No DOI found

Autism spectrum disorder in the second year: stability and change in syndrome expression - Chawarska, Katarzyna; Klin, Ami; Paul, Rhea; Volkmar, Fred (Journal of Child Psychology and Psychiatry, 2007)
Objectives: Increasing numbers of young children referred for a differential diagnosis of autism spectrum disorders (ASD) necessitates better understanding of the early syndrome expression and the utility of the existing state-of-the art diagnostic methods in this population. Method: Out of 31 infants under the age of 2 years referred for a differential diagnosis, 19 were diagnosed with autism, and 9 with pervasive developmental disorder-not otherwise specified (PDD- NOS) when reassessed at 3 years. We examined 1) the symptoms of ASD in the second year and changes in the syndrome expression by the age of three; 2) relationship between expert-assigned clinical diagnosis and diagnostic classification based on Autism Diagnostic Observation Schedule-Generic (ADOS-G) and Autism Diagnostic Interview-Revised (ADI-R) in the second year; 3) the relationship between direct observation and parental report of ASD symptoms. Results: Symptoms of autism and PDD- NOS in the second year were pronounced and stability of the clinical diagnosis was high. The agreement between clinician-assigned autism but not PDD- NOS diagnosis and the ADOS-G was high. However, sensitivity of the ADI-R diagnostic classification of autism was poor. Comparison of concurrent parental report and direct observation revealed discrepancies in severity ratings of key dyadic social behaviors. Changes in communication reflected acquisition of language accompanied by the emergence of unusual language characteristics. Symptoms of social dysfunction were relatively stable over time, and so was the severity of stereotyped behaviors. Conclusions: The study provides support for stability of clinical diagnosis and syndrome expression in the second year and highlights advantages and limitations of the ADI-R and ADOS-G for diagnosing and documenting symptoms of ASD in infants.
245 citations (Crossref) [2023-10-31] START/CPEA Network Meeting, Washington, DC, 2004 Citation Key Alias: lens.org/007-431-320-363-097 tex.unique-id: [object Object]
Keywords: ADI-R; ADOS-G; ASD; Assessment; Autism; Autistic Disorder; Child; Preschool; Communication; Diagnosis; Differential; Disease Progression; Early Diagnosis; Earlydiagnosis; Female; Humans; Infant; Infants; Interpersonal Relations; Language Development Disorders; Longitudinal studies; Male; PDD-NOS; Questionnaires; Social Behavior; Stereotyped Behavior; Toddlers; article; assessment; autism; communication disorder; controlled study; dept.cmd; differential diagnosis; disease severity; early diagnosis; female; follow up; human; infants; language disability; longitudinal studies; longitudinal study; male; observational study; patient referral; pervasive developmental disorder not otherwise specified; play; preschool child; psychologic assessment; psychological rating scale; sensitivity analysis; social behavior; social disability; social interaction; stereotypy; symptomatology; toddlers

Parental recognition of developmental problems in toddlers with autism spectrum disorders - Chawarska, Katarzyna; Paul, Rhea; Klin, Ami; Hannigen, Sarah; Dichtel, Laura E.; Volkmar, Fred (Journal of Autism and Developmental Disorders, 2007)
Symptoms of Autism Spectrum Disorders (ASD) begin to manifest during the first 2 years; there is limited evidence regarding type and timing of symptom onset. We examined factors related to parental age of recognition (AOR) of early abnormalities and the association between AOR and diagnosis and levels of functioning at 2 and 4 years in 75 toddlers with ASD. Results suggest significant differences between autism and PDD-NOS in the AOR and type of first concerns. Early social and motor delays as well as maternal age was associated with AOR. Later AOR was associated with poorer social-communicative and nonverbal cognitive functioning at 2 and 4. The findings are discussed in a context of identifying distinct developmental trajectories within the autism spectrum.
175 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-540-720-732-679 tex.unique-id: [object Object]
Keywords: Age Factors; Age of recognition; Autism; Autistic Disorder; Child; Preschool; Cognition Disorders; Developmental Disabilities; Early Diagnosis; Female; Follow-Up Studies; Humans; Infants; Male; Mass Screening; PDD-NOS; Parents; Recognition (Psychology); Regression; Severity of Illness Index; Social Behavior; article; autism; clinical feature; dept.cmd; developmental disorder; early diagnosis; functional assessment; human; major clinical study; maternal age; motor performance; nonverbal communication; parental attitude; peer-reviewed; preschool child; priority journal; social interaction